The effect of lactic exercises on some physical and functional variables of football players - Nayyef, Muayad nawfal; Abd, Zeyad Hameed; Hasan, Dunya Ali Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to know some of the physical and functional variables of soccer players (beginners) through the influence of lactic tolerance exercises, and the researchers used the experimental method by conducting a (pre-post) test to a sample of (20) players emerging from local clubs and were chosen intentionally and the most important results were An increase in the percentage of improvement in physical abilities between (3.28%, 16.98%) and an increase in the percentage of improvement in functional variables between (3.076% and 12.322%) .The researchers recommend using lactic tolerance exercises in the football training program to delay fatigue and raise the level of lactic tolerance in football.